The Caenorhabditis elegans Transgenic Toolbox - Nance, Jeremy; Frøkjær-Jensen, Christian (Genetics (Austin), 2019)
The power of any genetic model organism is derived, in part, from the ease with which gene expression can be manipulated. The short generation time and invariant developmental lineage have made Caenorhabditis elegans very useful for understanding, e.g., developmental programs, basic cell biology, neurobiology, and aging. Over the last decade, the C. elegans transgenic toolbox has expanded considerably, with the addition of a variety of methods to control expression and modify genes with unprecedented resolution. Here, we provide a comprehensive overview of transgenic methods in C. elegans, with an emphasis on recent advances in transposon-mediated transgenesis, CRISPR/Cas9 gene editing, conditional gene and protein inactivation, and bipartite systems for temporal and spatial control of expression.